The impact of digital transformation on corporate sustainability- new evidence from Chinese listed companies - Zhang, Chenxi; Chen, Pengyu; Hao, Yuanyuan (Frontiers in Environmental Science, 2022)
This paper evaluates the impact of digital transformation on business sustainability, explores whether digital transformation breaks down perceptions, and examines the mechanisms by which it works. First, we measured the digital transformation of each firm using textual analysis. and found that for every 1% increase in digital transformation, the sustainability of the business improved by 0.6%. Secondly, we found that digital transformation eases knowledge flow barriers and makes knowledge more accessible to firms. Firms with higher digital transformation attract more skilled people, which can create talent barriers. Digital transformation can exacerbate firms' industry monopolies, while increasing the proportion of boardroom women and the inclusion of older members sends positive signals to outsiders. Finally, we find that low costs, high labor productivity, high innovation and low cost of sales are important channels for digital transformation. In addition, digital transformation increases the management costs of firms.